(untitled) (Szociológiai Szemle, 2024)
Gypsies, or Roma, are simultaneously among history’s most romanticized and reviled of peoples. Stereotypically racialized and eroticized as "other" wherever they are located, prejudice and discrimination against Roma are currently heightened. This paper seeks to illustrate processes of identification by which Roma in post-socialist countries are classified as "other", as "different". Drawing on interview and observational data from the community studies of the project on "Poverty, Ethnicity, and Gender in Transitional Societies", this paper explores various discursive ways in which Roma are stereotypically "othered" by non-Roma populations as well as ways in which Roma understand themselves in relation to these historically persistent if situationally variable representations of their putative "identities". As is discussed, "Roma" as a category has been expanded in certain contexts to essentialize a purported relationship bewteen "race" and poverty.